2016
DOI: 10.1111/nmo.13005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of children with intractable functional constipation; experience of a single tertiary children's hospital

Abstract: Surgery can improve symptoms in children with intractable FC. Despite morbidity and complications, parental satisfaction is high. Prospective, high-quality research is necessary to develop guidelines for the diagnostic work-up and surgical management in children with intractable FC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…Depending on the results, intestinal diversion, various types of colectomy, and antegrade colonic enema (ACE) procedures have all proven to be beneficial, but the evidence supporting each of these is poor and larger, more rigorous studies are needed. [37, 38]…”
Section: Neurogenic Constipationmentioning
confidence: 99%
“…Depending on the results, intestinal diversion, various types of colectomy, and antegrade colonic enema (ACE) procedures have all proven to be beneficial, but the evidence supporting each of these is poor and larger, more rigorous studies are needed. [37, 38]…”
Section: Neurogenic Constipationmentioning
confidence: 99%
“…Currently, surgery of the colon is based on an extensive diagnostic workup including motility testing, often evaluated with colonic manometry. If colonic dysmotility is present, bypassing or removing the dysmotile colonic segment has been shown to be favorable for FC symptoms [67]. However, it has also been shown that dysmotility is potentially reversible and that motility, as measured by colonic manometry, can improve after decompression of the colon or after successful antegrade irrigation [68][69][70][71].…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…In early life, this phenomenon is usually associated with congenital organic diseases such as Hirschsprung's disease, anorectal malformations or other birth defects such as intestinal atresia . However, segmental colonic dilation can also be observed in older children with long‐standing symptoms of functional constipation (FC), in whom underlying organic pathology has been ruled out . The phenomenon of segmental dilation has also been described in adults and this has led to the definitions of megacolon and megarectum, defined by Preston et al.…”
Section: Introductionmentioning
confidence: 99%
“…The same may be true for colonic elongation . These observations have been utilized to advocate for surgical interventions (eg, partial resection of the dilated segment of the colon) . However, to date there is a lack of published data on the relationship between colonic dilation and colonic motility in children with FC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation